The economic toll of cancer: catastrophic expenditure and impoverishment among lower-income households in Malaysia - Farhana Aminuddin; Mohd Shaiful Jefri Mohd Nor Sham Kunusagaran; Sivaraj Raman; Marhaini Mostapha; Nur Amalina Zaimi; Tan Yui Ping; Mohd Shahri Bahari; Nur Azmiah Zainuddin; Nor Zam Azihan Mohd Hassan (BMC Public Health)
Abstract Background Cancer imposes a significant economic burden on patients and their families, often leading to catastrophic health expenditure (CHE) and impoverishment. This study assesses the financial strain faced by cancer patient households, particularly among lower-income populations, focusing on the catastrophic and impoverishing effects of cancer-related spending. Methods A cross-sectional study involving 430 cancer patients was conducted at six referral cancer centres across Malaysia from June to October 2022. Data on sociodemographic, out-of-pocket (OOP) cancer expenses, and household expenditure data were collected through face-to-face interviews. A three threshold levels were used to examine the CHE, with spending exceeding 10% of total household expenditure, or 25%, and 40% of non-food expenditure. The poverty headcount and gap were assessed by comparing pre- and post-OOP household income against the poverty line income (PLI). Multivariable logistic regression was used to identify determinants associated with CHE. Results The average total OOP costs were MYR4,388.65 (USD983.45) for early-stage cancers (Stages I-II) and MYR5,691.70 (USD1,275.45) for late-stage cancers (Stages III-IV). On average, OOP expenses constituted 17.4% of total household resources. The incidences of CHE at thresholds of 10%, 25%, and 40% were 67.2%, 48.8%, and 32.8%, respectively. Determinants significantly associated with CHE included age, ethnicity, cancer type, cancer stage, distance to cancer centre, household size, and household income. Pre-OOP, 52.6% of households were below the PLI, rising to 63.7% post-OOP, reflecting an 11.1% increase in the poverty headcount. The poverty gap widened, with a mean increase of MYR242.71 (USD54.39) between early- and late-stage cancers. Conclusions Although the public healthcare in Malaysia is highly subsidised, the lower-income households still face substantial CHE and poverty due to cancer-related OOP costs. Therefore, designing targeted policies and establishing comprehensive safety nets are essential to safeguard vulnerable households.